Erosion mechanisms and erosion products in tungsten targets exposed to plasma heat loads relevant to ELMS and mitigated disruptions in ITER - Safronov, V.M.; Arkhipov, N.I.; Klimov, N.S.; Landman, I.S.; Petrov, D.S.; Podkovyrov, V.L.; Poznyak, I.M.; Toporkov, D.A.; Zhitlukhin, A.M. (Національний науковий центр «Харківський фізико-технічний інститут» НАН України, 2010)
Tungsten targets were irradiated by intense plasma streams at plasma gun facilities MK-200UG and QSPA-T. The targets were tested by plasma loads relevant to Edge Localised Modes (ELM) and mitigated disruptions in ITER. Material erosion caused by melt motion and by emission of droplets has been studied. Мишени из вольфрама были подвергнуты воздействию интенсивных потоков плазмы на плазменных ускорителях МК-200UG и КСПУ-Т. Испытания проводились при плазменных нагрузках, характерных для ELMов и ослабленных срывов в ITERe. Исследована эрозия материала, обусловленная движением расплава и капельным разбрызгиванием. Мішені з вольфраму були піддані впливу інтенсивних потоків плазми на плазмових прискорювачах МК-200UG і КСПУ-Т. Іспити проводилися при плазмових навантаженнях, характерних для ELMів і ослаблених зривів в ITERі. Досліджено ерозію матеріалу, що обумовлена рухом розплаву і краплинним розбризкуванням. The work is supported by RFBR grant No 09-02-13562.